2015
DOI: 10.4238/2015.august.14.22
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-21 polymorphism and systemic lupus erythematosus: a meta-analysis

Abstract: ABSTRACT. Several case-control studies have been conducted to investigate the association between Interleukin-21 (IL-21) polymorphisms and systemic lupus erythematosus (SLE) susceptibility, and most of the studies focused on IL-21 rs907715 and rs2221903 polymorphisms. Given the inconsistent results from these studies, the present meta-analysis aimed to obtain a more precise estimate of the association between IL-21 rs907715 and rs2221903 polymorphisms and SLE. Studies regarding these specific polymorphisms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Previous reports showed that SNPs in the IL-21 gene, such as rs907715 and rs2221903, increased susceptibility to Grave's disease [32,33] and systemic lupus erythematosus (SLE) in the Europeans and Americans [34,35], as well as the Chinese [20,36,37]. Moreover, IL-21 rs4833837 SNP was identified as a protective factor for psoriasis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that SNPs in the IL-21 gene, such as rs907715 and rs2221903, increased susceptibility to Grave's disease [32,33] and systemic lupus erythematosus (SLE) in the Europeans and Americans [34,35], as well as the Chinese [20,36,37]. Moreover, IL-21 rs4833837 SNP was identified as a protective factor for psoriasis [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are increased IL-21producing peripheral CD4 + T cells in SLE patients, correlating with a concurrent increase in memory B cells and Th17 cells and reduced Treg cells [137]. Genetic variants in the IL-21 gene are noted to be associated with SLE [138,139]. A recent clinical trial of an IL-21 inhibitor, NNC0114-0006, has been terminated according to ClinicalTrials.Gov.…”
Section: Il-21mentioning
confidence: 99%
“…34 Previous studies have found that polymorphisms of IL-21 gene have significant association with autoimmune diseases including SLE, rheumatoid arthritis (RA), and multiple sclerosis. 17,3537 The results of our study suggested that polymorphisms upstream of this gene also have a potential risk effect on SLE, and we found, for the first time, that rs11937669 and rs11725913 were associated with SLE susceptibility in the Chinese Han population, with T and G allele, respectively, being potential risk alleles. Moreover, we described an interesting relationship between SNP rs11937669 and levels of Th17-related cytokines in SLE patients.…”
Section: Discussionmentioning
confidence: 50%